2018
DOI: 10.1111/acem.13361
|View full text |Cite
|
Sign up to set email alerts
|

Key High‐efficiency Practices of Emergency Department Providers: A Mixed‐methods Study

Abstract: Average patient load, running the board, conversations with team member, and using names of team members are associated with enhanced provider productivity. Identification of behaviors associated with efficiency can be utilized by medical directors, clinicians, and trainees to improve personal efficiency or counsel team members.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…The skill required for managing busy and complex systems are undoubtedly important for attending emergency physicians (EPs), but these skills are currently heterogeneously taught. While there is new and intriguing evidence around EP efficiency, 18 there is still little by way of formal teaching reported within our current study. However, it is not surprising that a fair number of informal and experiential in situ instructional methods have crystallized under the increasing pressures of overcrowded ED systems.…”
Section: Discussionmentioning
confidence: 61%
“…The skill required for managing busy and complex systems are undoubtedly important for attending emergency physicians (EPs), but these skills are currently heterogeneously taught. While there is new and intriguing evidence around EP efficiency, 18 there is still little by way of formal teaching reported within our current study. However, it is not surprising that a fair number of informal and experiential in situ instructional methods have crystallized under the increasing pressures of overcrowded ED systems.…”
Section: Discussionmentioning
confidence: 61%
“…Much of the previous literature on clinical productivity described system-based approaches rather than individual-based strategies [6-9]. Few articles have formally examined clinical productivity best practices among practitioners in the emergency department [10,11]. While our methodology was more formal, many of the themes identified in our study overlap with those found in the literature.…”
Section: Discussionmentioning
confidence: 90%
“…We sought to develop a greater understanding of the efficiency strategies that these EPs used to function at such a high level. Unfortunately, previous productivity studies in emergency medicine have focused on department-wide efficiency [6-9] and only rarely have provided guidance on improving individual productivity [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…13 It has been suggested that when first names are used, teams work more efficiently and that this has positive implications for patient safety. 14 Root cause analysis has demonstrated up to 70% of adverse events are due to communication failure. Medical and nursing teams already recognise this; in one survey, two-thirds of staff felt communication was the most important factor in improving efficiency and safety.…”
Section: Discussionmentioning
confidence: 99%